DETERMINANTS OF BANKING BUSINESS TRANSFORMATION DURING THE COVID -19 PERIOD - Dharma Triadi Yunus; Herlin Tundjung Setijaningsih (International Journal of Application on Economics and Business, 2024)
The purpose of this research is to obtain empirical evidence about the effects of intellectual capital measured by human capital efficiency (HCE), structured capital efficiency (SCE), and capital employed efficiency (CEE) on financial performance in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. This research uses 46 samples and 138 data from banking companies selected by the purposive sampling method. Data processing techniques uses multiple linear regression and processed using Eviews version 12. The result of this research indicates that HCE has a negative and significant effect on financial performance, SCE has a negative and significant effect on financial performance, CEE has a positive and significant effect on financial performance.